Three new species of Evolvulus (Convolvulaceae) from Bahia, Brazil - Da Silva, Cintia Vieira; Simão-Bianchini, Rosangela (Phytotaxa, 2014)
The semi-arid region of Bahia is rich in species of Convolvulaceae, particularly in the genera Evolvulus, Ipomoea, and Jacquemontia. Field work in this region and taxonomic revision of Evolvulus section Phyllostachyi revealed the occurrence of three new species: Evolvulus altissimus, the tallest species of the genus, is a subshrub up to two metres tall; Evolvulus delicatus is a flexible branched species with small, stiff, and narrow pointed leaves; Evolvulus harleyi is a herb with glabrous or nearly glabrous leaves and a globose inflorescence. These three species are described and illustrated. Their similarities with allied taxa are discussed. A região do semi-árido da Bahia é rica em espécies de Convolvulaceae, particularmente os gêneros Evolvulus, Ipomoea e Jacquemontia. Diversos trabalhos de campo nesta região para a revisão taxonômica de Evolvulus seção Phyllostachyi revelaram a ocorrência de três novas espécies: Evolvulus altissimus, a mais alta dentre todas as espécies do gênero, é um subarbusto de até dois metros de altura; Evolvulus delicatus é uma espécie de ramos flexíveis com folhas pequenas, estreitas, duras e pontiagudas; Evolvulus harleyi é uma erva com folhas glabras ou quase glabras e inflorescência globosa. Estas três espécies são descritas e ilustradas. As relações com espécies próximas são discutidas.